2014
DOI: 10.1007/s11661-014-2681-7
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Intrinsic Nanohardness of Lath Martensite in Low Carbon Steel

Abstract: The mechanical property of martensite blocks in low carbon steel is studied by nanoindentation combined with scanning electron microscopy, electron backscattered diffraction, and transmission electron microscopy. The average nanohardnesses of small and large martensite blocks are 6.9 and 5.4 GPa, respectively. A size effect that the smaller is stronger is thus observed. This size effect was ascribed to the different formation sequence of martensite blocks during quenching. Therefore, the present work suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Li et al [5] showed that the nanohardness within the martensite studied can vary between 5 GPa and 11 GPa. It has been observed that the smaller blocks (aggregate of laths with low angle misorientation) have a higher hardness in [6] with an average nanohardness of about 5.5 GPa for the large blocks and 6.9 GPa in the small blocks with a width estimated by Electron Backscattered Diffraction (EBSD) equal to 6 and 3.5 μm respectively. He et al [7] studied ferritic microstructures (ferrite, lower and upper bainite, and martensite) highlighting a significantly wider scattering in the martensite results.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [5] showed that the nanohardness within the martensite studied can vary between 5 GPa and 11 GPa. It has been observed that the smaller blocks (aggregate of laths with low angle misorientation) have a higher hardness in [6] with an average nanohardness of about 5.5 GPa for the large blocks and 6.9 GPa in the small blocks with a width estimated by Electron Backscattered Diffraction (EBSD) equal to 6 and 3.5 μm respectively. He et al [7] studied ferritic microstructures (ferrite, lower and upper bainite, and martensite) highlighting a significantly wider scattering in the martensite results.…”
Section: Introductionmentioning
confidence: 99%
“…The martensite in the dark regions was supposed to be formed at a later stage of martensite transformation, which maintained a high dislocation density. The martensite in the light-color regions was supposed to be formed at the beginning of the martensite formation with a relatively high temperature and exhibited reasonably low dislocation density because of greater recovery of dislocations throughout the extended period of transformation [18]. At the same time, residual austenite gradually transformed into martensite that is dark.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the grain refinement hardly affects the lath width of martensite [ 64 ]. Considering the lath width of martensite in low C steel (100 nm to 500 nm) [ 65 ], it is reasonable to expect that the grain refinement plays a vital role in stabilizing the ultrafine austenite grain (<0.5 μm). This is confirmed from the experimental work on medium Mn steel, where the optimal austenite grain size is 0.5–0.6 μm [ 63 , 66 ].…”
Section: The Factors Govern Austenite Stabilitymentioning
confidence: 99%
“…It is found that the amount of martensite transformed close to the free surface is larger than the bulk interior owing to the lack of constraint from adjacent grains [ 121 ]. In particular, it is expected that the influence of free surface on the austenite stability is severe under in situ TEM observation, as the thickness of the TEM sample should be as thin as around 100 nm to allow the transmission of electron, and such a thickness is even smaller than the width of lath martensite (~100−500 nm) [ 65 ]. In other words, the observation of the martensitic transformation in metastable austenite grains using microscopy such as the TEM observation may undesirably involve the effect of the free surface [ 129 , 174 , 175 ].…”
Section: Characterization Techniquesmentioning
confidence: 99%